A Case Control Study on Risk Factors and Drug Prescription Patterns in Glaucoma at a tertiary eye care center in a city of Western India - Sanket P. Bharadwaj; Kavisha S. Goswami; Kintu S. Shah; Reema M. Raval; Aparajita A. Shukla (Indian Association of Preventive and Social Medicine, 2023)
Introduction: Glaucoma is an idiopathic, progressive optic disc neuropathy complicating into irreversible blindness if untreated. Early diagnosis by screening cases from high-risk populations has a pivotal role in managing this major public health problem with high treatment expenditures. Objectives: To identify the various ocular and non ocular risk factors of glaucoma and to identify the drug prescription pattern among glaucoma patients.Method: This was an observational, case-control study including 165 adult Glaucoma patients on treatment as cases and 165 age and sex-matched healthy individuals as controls, all of which were randomly selected from the patients visiting a tertiary eye care center. Various risk factors, drug prescription pattern and symptoms of the patients were recorded and analyzed.Results: A total of 165 adult Glaucoma patients and age and gender matched 165 controls were enrolled. Majority of the patients (41.21%) complained of blurring of vision at the time of study. The Odds ratios for Family history, Hypertension, Diabetes Mellitus, Migraine, Sleep apnea and Smoking showed strong association as risk factors for Glaucoma and the differences between the two groups were statistically significant (p value < 0.05). The mean number of drugs per prescription ± SD was 1.88 ± 0.79. Fixed drug formulations were prescribed in 42.4% patients. All the drugs were prescribed by their brand names and majority of them were in the form of eye drops.Conclusion: Primary Open Angle Glaucoma (POAG) was the most common subtype in the study. Age, Family history, Myopia, Hypertension, Diabetes Mellitus, Sleep Apnea, Migraine, Corticosteroid usage and Smoking emerged as putative risk factors. In consistence with present guidelines, Prostaglandin analogs were the most prescribed antiglaucoma drugs. The considerable proportion of asymptomatic cases (23%) suggests the need for periodic eye examinations to detect glaucomatous changes at an early stage